Deset romanov Ivana Cankarja in sodobna definicija romana - Zupan Sosič, Alojzija (Slavia Centralis, 2020)
TEN NOVELS BY IVAN CANKAR AND A CONTEMPORARY DEFINITION OF THE NOVEL This is a list of ten of Cankar’s novels that were labelled as stories or novellas in the past and which I have now reclassified as novels with the help of the contemporary definition: Tujci (1901), Na klancu (1902), Hiša Marije Pomočnice (1904), Gospa Judit (1904), Križ na gori (1904), Martin Kačur (1906), Nina (1906), Novo življenje (1908), Milan in Milena (1913), Marta (unfinished novel). The (transitional) definition isthe result ofscientific insight into European-American history and the theory of the novel. My conclusion is that the syncretism of forms and genre syncretism are the most important for this type of Cankar’s novels. While the former loosensthe epic core, the latter introduces amixture of different genres, most of them completely innovative for the Slovenian area. Cankar was not only innovative in the modernisation of his novels but also with their classification: he defines all ten works as novels, which has only happened in literary science in this study.